Strengthening Democracy and Law Post The 2024 Elections in Indonesia - Willy Aditya; Syaiful Rohman (West Science Law and Human Rights, 2024)
A strong democracy will create broader public participation in the development process through transparent and accountable democratic mechanisms. Thus, democracy is a political system that ensures inclusive and sustainable economic growth and creates solid social stability. As individuals and communities, we are responsible for strengthening democracy to realize equitable and sustainable national development through active involvement in democratization and support for policies that favor social justice and shared prosperity. After the 2024 elections, polarization in society due to the power struggle is still felt, so the role of political parties and the government is crucial in maintaining political stability and the country's future development. This research will analyze the factors that can be used to strengthen democracy. The results show that the rule of law determines the process of strengthening democracy, the role of political parties, community involvement, and the professionalism of election organizers to achieve common goals and national progress.